1, 10-Phenanthroline-Catalysed Cr(VI) Oxidation of D-Sorbitol and D-Mannitol in Aqueous Micellar Media. (3rd June 2009) - Bayen, Ruhidas; Das, Asim
Chromic acid oxidation of two polyols (D-sorbitol and D-mannitol) to their corresponding aldohexoses in the presence of phenanthroline (phen) involves as the active oxidant, a Cr(VI)-phen complex formed in a rapid pre-equilibrium step. The observed micellar effect (rate acceleration by an anionic surfactant and rate retardation by a cationic surfactant) conforms with the proposed reaction mechanism.